2020
DOI: 10.1371/journal.pone.0230812
|View full text |Cite
|
Sign up to set email alerts
|

Combination of organic acids and low-dose gamma irradiation as antimicrobial treatment to inactivate Shiga toxin-producing Escherichia coli inoculated in beef trimmings: Lack of benefits in relation to single treatments

Abstract: The aim of this study was to assess the efficacy of lactic acid (LA), caprylic acid (CA), high-(HDI) and low-(LDI) dose gamma irradiation and LDI combined with LA or CA on the inactivation of a pool of Shiga toxin-producing Escherichia coli (STEC) strains inoculated on beef trimmings. The three most efficacious treatments were selected to study their effect on meat quality parameters and sensory attributes. The inoculum included five native STEC serogroups (O26, O103, O111, O145 and O157). The treatments appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…However, it was only possible to reduce less than 1 log of STEC. In Argentina, 2 log STEC/g reductions were obtained under experimental conditions in beef trimmings using high and low dose gamma irradiation (Cap et al, 2020). In addition, 5 log UFC STEC/g reductions were obtained in ground beef experimentally contaminated (Cap, 2020, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was only possible to reduce less than 1 log of STEC. In Argentina, 2 log STEC/g reductions were obtained under experimental conditions in beef trimmings using high and low dose gamma irradiation (Cap et al, 2020). In addition, 5 log UFC STEC/g reductions were obtained in ground beef experimentally contaminated (Cap, 2020, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…In the present model, treatment with organic acids and hot water improved the quality of the meat produced in abattoirs, which would result in an improvement in public health. Among physical interventions, gamma irradiation is a well-known, safe and effective method for controlling microorganisms (Cap et al, 2020; Sommers et al, 2015; Xavier et al, 2014). In the scenario analysis of ground beef and hamburgers, it was demonstrated that the irradiation treatment would reduce 93.1 times the risk of HUS compared with the baseline scenario and considering the different population groups.…”
Section: Discussionmentioning
confidence: 99%
“…The Effect of irradiation on HUS probability from hamburger consumption was modeled using data reported by Cap et al (2020). These authors showed a net STEC >5 log CFU/g reduction (7 log CFU/ g before and < 2 CFU/g after the intervention) with the application of 0.23 kGy.…”
Section: Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In selective media like MCA, only viable bacteria can form colonies. The difference between the two media counts were determined as injured cells (Cap et al., 2020a, b; Eccoña Sota et al., 2021; Espina et al., 2016). One the other hand, lethality was calculated as the difference between TSA counts of the HPP‐treated samples and TSA counts of control ones.…”
Section: Methodsmentioning
confidence: 99%